THE ANALYSIS RICE PREFERENCE IN BANDUNG - Shafira, Azalia; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2017)
Abstract. Indonesia is the 3rd largest rice producer in the world with 71 million ton rice production a year and 47 million ton rice consumption a year. Even though the production is bigger than the consumption, 472 hundred ton rice is still imported to Indonesia. The data of the rice imports reveals the failure of the local rice production in fulfilling the consumption of Indonesian society. This is partly due to the society’s preference of rice type which is not met with the type produced locally. This phenomenon also demonstrates that a study of society’s rice preference is significant in achieving the national rice consumption sufficiency. So, This research will address the preference of rice consumer in Bandung by analysing the market structre of rice by in depth interview method and questionnaire deployment to the consumer. Then, all the data from the rice consumer is processed through conjoint analysis and cross tabulation chi square to get the real insight of customer preference.The research find most of the respondent preferred to buy a rice which is white clean color, usual brand,not containing lice, the price is about Rp 9000-Rp 15000, and the type of the rice is Pandan Wangi. For Pandan Wangi itself their willingness to buy is quite high especially their willingness to recommend it to their relatives.This research is important to understand the society's rice preference in Bandung in order to improve the distribution process so that the rice demand can be fulfilled appropriately. Keywords:  rice market structure, rice preference, consumer behavior, Pandan Wangi, conjoint analysis